Pelatihan Pengelolaan Keuangan Dalam Rangka Meningkatkan Kesejahteraan - Aulia, Azwani; Purwanto, Eko; Lestari, Putri Gantine; Heriyah, N.; Himmah, Elok Faiqoh; Dianty, Astari; Siregar, Johannes Kristian; Putri, Anike; Meila, Kaca Dian; Bimo, Antonius (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
This community service activity aims to improve the financial well-being of Indonesian kindergarten teachers through financial management training. The COVID-19 pandemic has significantly impacted the education sector, particularly for kindergarten teachers who have experienced a decline in income due to a reduced number of students and parents' inability to pay school fees. Through this training, participants were provided with knowledge and skills in personal financial management, budgeting, financial reporting, and investment strategies. The results of this activity showed an increase in participants' knowledge and awareness of the importance of financial literacy to maintain financial well-being during difficult times. Active participation in simulations and interactive discussions reflected the success of this training. Evaluation was conducted through quizzes and discussions to gather feedback for future training improvements.